Ginzburg-Landau approach to the vortex–domain wall interaction in superconductors with nematic order - Severino, Ramiro Sebastian (2024)
In this work, we study the interaction between vortices and nematic domain walls within the framework ofa Ginzburg-Landau approach. The free energy of the system is written in terms of a complex order parametercharacteristic of s-wave superconductivity and a real (Ising-type) order parameter associated with nematicity.The interaction between both order parameters is described by a biquadratic and a trilinear derivative term. Tostudy the effects of these interactions, we solve the time-dependent dissipative Ginzburg-Landau equations usinga highly effective pseudospectral method by which we calculate the trajectories of a vortex that, for differentcoupling parameters, is either attracted or repelled by a wall, as well as of the wall dynamics. We show thatdespite its simplicity, this theory displays many phenomena observed experimentally in Fe-based superconductors. In particular, we find that the sign of the biquadratic term determines the attractive (pinning) or repulsive(antipinning) character of the interaction, as observed in FeSe and BaFeCoAs compounds, respectively. Thetrilinear term is responsible for the elliptical shape of vortex cores as well as the orientation of the axes ofthe ellipses and vortex trajectories with respect to the axes of the structural lattice. For the case of pinning, weshow that the vortex core is well described by a heart-shaped structure in agreement with scanning tunnelingmicroscopy experiments performed in FeSe.